In situ experimental evidences for responses of abyssal benthic biota to shifts in phytodetritus compositions linked to global climate change. (23rd September 2021) - Nomaki, Hidetaka; Rastelli, Eugenio; Ogawa, Nanako O.; Matsui, Yohei; Tsuchiya, Masashi; Manea, Elisabetta; Corinaldesi, Cinzia; Hirai, Miho; Ohkouchi, Naohiko; Danovaro, Roberto; Nunoura, Takuro; Amaro, Teresa
Abstract: Abyssal plains cover more than half of Earth's surface, and the main food source in these ecosystems is phytodetritus, mainly originating from primary producers in the euphotic zone of the ocean. Global climate change is influencing phytoplankton abundance, productivity, and distribution. Increasing importance of picoplankton over diatom as primary producers in surface oceans (especially projected for higher latitudes) is projected and hence altering the quantity of organic carbon supplied to the abyssal seafloor as phytodetritus, consequences of which remain largely unknown. Here, we investigated the in situ responses of abyssal biota from viruses to megafauna to different types of phytoplankton input (diatoms or cyanobacteria which were labeled with stable isotopes) at equatorial (oligotrophic) and temperate (eutrophic) benthic sites in the Pacific Ocean (1°N at 4277 m water depth and 39°N at 5260 m water depth, respectively). Our results show that meiofauna and macrofauna generally preferred diatoms as a food source and played a relatively larger role in the consumption of phytodetritus at higher latitudes (39°N). Contrarily, prokaryotes and viruses showed similar or even stronger responses to cyanobacterial than to diatom supply. Moreover, the response of prokaryotes and viruses was very rapid (within 1–2 days) at both 1°N and 39°N, with quickest responses reported in the case of cyanobacterial supply at higher latitudes. Overall, our results suggest that benthic deep‐sea eukaryotes will be negatively affected by the predicted decrease in diatoms in surface oceans, especially at higher latitudes, where benthic prokaryotes and viruses will otherwise likely increase their quantitative role and organic carbon cycling rates. In turn, such changes can contribute to decrease carbon transfer from phytodetritus to higher trophic levels, with strong potential to affect oceanic food webs, their biodiversity and consequently carbon sequestration capacity at the global scale. Abstract : Schematic view of the natural settings of both 39°N and 1°N sites at western Pacific abyssal plain, as well as a synoptic view of the main highlights from the in situ incubation experiments conducted in this study on the responses of benthic biota to different phytoplankton supplies linked to global climate change. Benthic deep‐sea eukaryotes will be negatively affected by the predicted decrease in diatoms in surface oceans, especially at higher latitudes, while prokaryotes and viruses will otherwise likely increase their quantitative role and organic carbon cycling rates.